PROFIL VITAMIN D PADA PASIEN ASMA DAN NON-ASMA DEWASA DI SURABAYA - Rivan Virlando Suryadinata; Amelia Lorensia; Anugrah Putri Aprilia (Universitas Airlangga, 2017)
Asthma is a chronic inflammatory disease on respiratory tract, where airflow are retricted dan chronic inflammation result in bronchial epithelium damage. Pathogenesis mechanism of asthma is influenced by vitamin D as an immunomodulator. The low vitamin D levels can trigger asthma exacerbations. The study aimed to determine the levels of vitamin D from blood sample in astmatic young adult in compared to non astmatics, to identify the risk of vitamin D deficiency, that can aggravate asthma symptoms. The study used an observational analytic cross sectional design. Subjects were chosen through a purposive sampling method. Population was young adults in Surabaya. Subjects were 26 asthmatic patientsdan 26 non-asthmatic young adult in South Surabaya that fulfilled inclusion dan exclusion criteria. The study was conducted in May 2015 to July 2016. The results showed vitamin D levels in the asthma group 24.5 ± 2.95 while in the non-asthma group 20.52 ± 2.47. All respondents in both groups had vitamin D levels > 30 ng/mL (normal value), dan there was significant difference between levels of vitamin D in asthma dan non-asthma patients (p < 0.05). Therefore, increasing knowledge about the importance of vitamin D should be done, because it can change behavior through lifestyle, diet dan physical activity in the community. Keywords: asthma, vitamin D